In silico tools for mechanical analysis of extra‐ and intra‐luminal artificial urinary sphincters - Gianluca Mazzucco; Paola Pirini; Chiara Giulia Fontanella; Alice Berardo; Maria Vittoria Mascolini; Ilaria Toniolo; Leonardo Marziale; Tommaso Mazzocchi; Gioia Lucarini; Nicolò Spiezia; Emanuele Luigi Carniel (BJUI Compass)
Abstract Objectives To analyse and compare the functionality of extraluminal and intraluminal artificial urinary sphincters (AUSs), an in silico procedure has been defined and applied. Design and reliability assessments of the AUS are typically performed using a clinical approach, which does not provide data on mechanical stimulation of urethral tissues. Mechanical stimulation may determine tissue degeneration, such as urethral atrophy or erosion, the main causes of AUS failure. In silico techniques can provide a quantitative description of stress and strain fields due to the interaction between tissues and AUS and allow investigating an extremely large number of situations, considering different configurations of AUS and urethra. Materials and Methods Computational investigations were carried out to evaluate the mechanical reliability of the main extraluminal and intraluminal AUS, AMS 800 and Relief. The lower urinary tract was modelled based on previous experiments. The AUS models took into account the main components that interact with biological tissues. Urethra and AUS models were coupled and used to investigate mechanical stimulation of urethral tissues. Results In silico simulations provide quantitative information about the mechanical stimulation of urethral tissue, such as compressive strain and stress and hydrostatic pressure, due to interaction with the AUS. Such mechanical quantities allow a comparison of reliability between extraluminal and intraluminal devices. Conclusions The activities define and demonstrate the effectiveness of a novel in silico approach to the design and reliability assessment of AUS devices, increasing the investigative possibilities and reducing the time, ethical and economic costs.